Вивчення контрольованого електронного переносу крізь одиночну органічну молекулу - Василюк, Світлана Вікторівна; Мягченко, Юрій Олександрович (НТУ "ХПІ", 2016)
Ціль дослідження полягає в тому, щоб вивчити квантовані стабільні стани на графіку залежності опору органічних молекул від часу, поміщених між механічно контрольованими наноконтактами при заданому значенні сили струму. Передбачається знайти найбільш придатні діапазони значень опору для наступного одержання вольт-амперних характеристик досліджуваних нових органічних речовин для молекулярної електроніки.

The purpose of research will be to study the quantum stable states on the dependence schedule of organic molecules resistance versus time, placed between mechanically controllable break junctions at a present value of current. It is supposed to find the most suitable ranges of resistance values for the subsequent reception current versus voltage characteristics of the researched new organic substances necessary for molecular electronics requests. Organic semiconductors can be defined as solid, containing a significant amount of carbon-carbon bonds that are capable of supporting electronic conductivity. At this time, it became possible to synthesize semiconductors with desired electrical properties using organic chemistry, contributing to the rapid development of this area. It was possible to obtain substances with a wide range of mechanical properties by preparing specific molecular structures. If this possibility can be spread on electrical parameters, it will lead to increasing use of semiconductors beyond the use of industrially important inorganic semiconductors like silicon and germanium.
Controlled study of electron transport through single organic molecule
Keywords: молекулярна електроніка; нанотехнологія; квантова хімія; одномолекулярний транзистор; molecular electronics; nanotechnology; quantum chemistry